The impact of externally instigated separatism on the political stability and territorial integrity of countries - Лисянський, Павло Леонідович; Лисянський, П. Л.; Lysianskyi, Pavlo L.; Ястребова, Віра Андріївна; Ястребова, В. А.; Yastrebova, Vira A.; Iastrebova, Vira; Мамонтова, Елла Вікторівна; Мамонтова, Е. В.; Mamontova, Ella V.; Саліхов, Артем Романович; Саліхов, А. Р.; et al. (Porto : Universidade Portucalense Infante D. Henrique, 2024)
This study seeks to define the core concept of externally instigated separatism (EIS) and identify mechanisms to prevent and mitigate its adverse consequences. The research methodology is based on structural, logical and systemic analysis methods. The global system of law and order enshrines peoples' right to self-determination, guaranteed by states and the international community. Externally instigated separatism is a mechanism of direct aggression employed by states aiming to annex new territories. It represents a stage in hybrid warfare, characterized by the exogenous influence of actors supported by one state operating within another’s territory. The greatest threat of externally instigated separatism is seen in the level of integration of such actors into the socio-political environment of the state. This means increased opportunities for these actors to subvert the security environment of the state through direct incitement to separatist movements. That is why timely identification of manifestations of externally instigated separatism is critical to stabilizing the situation inside the country and preserving its sovereignty and territorial integrity. The article proves the need to develop a state strategy for counteracting externally instigated separatism.
Lysianskyi P. The impact of externally instigated separatism on the political stability and territorial integrity of countries / P. Lysianskyi, V. Iastrebova, E. Mamontova et al. // Revista Jurídica Portucalense. – Porto : Universidade Portucalense Infante D. Henrique, 2024. – 36. – P. 599-623. URL: https://doi.org/10.34625/issn.2183-2705(36)2024.ic-26
Keywords: externally instigated separatism; hybrid warfare; exogenous influence; threat matrix; separatist movements